The Role of S100A12 as a Systemic Marker of Inflammation - B. Meijer; R. B. Gearry; A. S. Day (International Journal of Inflammation)
S100A12 is a member of the S100 family of calcium-binding proteins with important extracellular activities. In recent years, investigators across a number of fields have delineated the patterns of S100A12 expression in a variety of conditions. These data suggest that S100A12 can be used as a valuable serum inflammatory marker.